Molecular cloning, modeling and site-directed mutagenesis of type III polyketide synthase from Sargassum binderi (Phaeophyta) - Baharum, Hariyanti; Morita, Hiroyuki; Tomitsuka, Akifumi; Lee, Fong Chin; Ng, Kim Yong; Abdul Rahim, Raha; Abe, Ikuro; Ho, Chai Ling (Springer New York LLC, 2011)
Type III polyketide synthases (PKSs) produce an array of metabolites with diverse functions. In this study, we have cloned the complete reading frame encoding type III PKS (SbPKS) from a brown seaweed, Sargassum binderi, and characterized the activity of its recombinant protein biochemically. The deduced amino acid sequence of SbPKS is 414 residues in length, sharing a higher sequence similarity with bacterial PKSs (38% identity) than with plant PKSs. The Cys-His-Asn catalytic triad of PKS is conserved in SbPKS with differences in some of the residues lining the active and CoA binding sites. The wild-type SbPKS displayed broad starter substrate specificity to aliphatic long-chain acyl-CoAs (C6–C14) to produce tri- and tetraketide pyrones. Mutations at H331 and N364 caused complete loss of its activity, thus suggesting that these two residues are the catalytic residues for SbPKS as in other type III PKSs. Furthermore, H227G, H227G/L366V substitutions resulted in increased tetraketide-forming activity, while wild-type SbPKS produces triketide α-pyrone as a major product. On the other hand, mutant H227G/L366V/F93A/V95A demonstrated a dramatic decrease of tetraketide pyrone formation. These observations suggest that His227 and Leu366 play an important role for the polyketide elongation reaction in SbPKS. The conformational changes in protein structure especially the cavity of the active site may have more significant effect to the activity of SbPKS compared with changes in individual residues.